Alcohol Consumption and Risk of Cardiovascular Disease and Death in Women - Luc Djoussé; I‐Min Lee; Julie E. Buring; J. Michael Gaziano (2009)
Background— Although an association between moderate alcohol consumption and decreased cardiovascular disease (CVD) and death has been reported, limited data are available on potential mediating mechanisms. We examined the association between alcohol and CVD and death in 26 399 women and estimated the proportion of reduced risk of CVD/death explained by a series of intermediate factors. Methods and Results— Alcohol consumption was self-reported at baseline, and CVD events and deaths were ascertained via follow-up questionnaires and medical records. Baseline levels of hemoglobin A1c, inflammatory markers, hemostatic factors, and lipids were measured. Blood pressure and hypercholesterolemia and treatment for lipids were self-reported. During a mean follow up of 12.2 years, 1039 CVD events and 785 deaths (153 CVD deaths) occurred. There was a J-shaped relation between alcohol consumption and incident CVD and total and CVD deaths in a multivariable model. Compared with abstainers, alcohol intake of 5 to 14.9 g/d was associated with 26%, 35%, and 51% lower risk of CVD, total death, and CVD death, respectively, in a multivariable model. For CVD risk reduction, lipids made the largest contribution to the lower risk of CVD (28.7%), followed by hemoglobin A1c/diabetes (25.3%), inflammatory/hemostatic factors (5%), and blood pressure factors (4.6%). All these mediating factors together explained 86.3%, 18.7%, and 21.8% of the observed lower risk of CVD, total death, and CVD death, respectively. Conclusions— These data suggest that alcohol effects on lipids and insulin sensitivity may account for a large proportion of the lower risk of CVD/death observed with moderate drinking under the assumption that the alcohol-CVD association is causal.